Aging-related fears and their associations with ideal life expectancy - Rupprecht, Fiona; Martin, Kristina; Lang, Frieder (European Journal of Ageing, 2021)
Fears regarding various aspects tend to stimulate individuals to escape or to avoid the sources of the threat. We concluded that fears associated with the future aging process, like the fear of aging-related diseases, the fear of loneliness in old age, and the fear of death, would stimulate patterns of avoidance when it comes to ideal life expectancy. We expected fear of aging-related diseases and fear of loneliness in old age to be related to lower ideal life expectancies. We expected fear of death to be related to higher ideal life expectancies. In two adult lifespan samples [N1 = 1065 and N2 = 591; ages ranging from 18 to 95 years, M (SD)1 = 58.1 (17.2) years, M (SD)2 = 52.6 (18.1) years], we were able to support our hypothesis regarding fear of death. We furthermore found significant interactions among the fears, indicating that individuals fearing diseases or loneliness but being unafraid of death opted for the shortest lives. Our results indicate that fears regarding life in very old age might be associated with the wish to avoid this age period; the fear of death was however associated with the wish for particularly long lives, and thus, with distancing oneself from the dreaded event of death. We conclude that fears seem to be associated with how individuals approach old age and with what they wish for in their own future as aged people.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Aging-related fears; Fear of death; Ideal life expectancy; Longevity desires

COVID-19 and Perceiving Finitude: Associations With Future Time Perspective, Death Anxiety, and Ideal Life Expectancy - Rupprecht, Fiona; Martin, Kristina; Kamin, Stefan; Lang, Frieder (Psychology and Aging, 2021)
The coronavirus pandemic threatens the health, future, and life of individuals and might hence accentuate perceptions of the fragility and finitude of life. We investigated how different perceptions of the pandemic (regarding the virus as a health threat and perceiving social and financial restrictions due to the pandemic) relate to different perceptions of life’s finitude (i.e., future time perspective, death anxiety, and ideal life expectancy). Using longitudinal data from 1,042 adults (68% women; aged 18–95 years) gathered within the first and within the second peak of the pandemic in Germany, we expected decreases in future time perspective and ideal life expectancy, as well as increases in death anxiety in response to threatening perceptions of the pandemic. The results indicated decreasing future time perspectives, an accentuation of death anxiety right at the beginning of the pandemic, as well as stable ideal life expectancies. There was a tendency for more pronounced change among older adults. Initial levels and changes in the perceptions of finitude could partly be explained by initial and changing perceptions of the pandemic. Next to perceptions targeting the threat of the virus itself, perceptions of strong social and financial restrictions during the pandemic contributed to an altered stance toward the finitude of life. Concluding, we discuss stability and variation in perceptions of the finitude of life during a time of major societal change and a potentially lifethreatening pandemic.
CRIS-Team Scopus Importer:2021-12-17
Keywords: coronavirus pandemic; death anxiety; finitude of life; future time perspective; ideal life expectancy

COVID-19 Worries Predict Aging Preparation: Culture- and Domain-Specific Perspectives - Kim-Knauß, Yaeji; Lang, Frieder; Rupprecht, Fiona; Martin, Kristina; Fung, Helene H. (The journals of gerontology. Series B, Psychological sciences and social sciences, 2022)
OBJECTIVES: We investigated whether worrying about coronavirus disease 2019 (COVID-19) predicts people's engagement in aging preparation. Furthermore, we expected that this association would have culture- (i.e., Hong Kong and Germany) and domain-specific (i.e., finances, housing, care needs, connectedness, and end-of-life) tendencies, as the culture and domains that are most severely hit by the pandemic differ. METHODS: A total of 360 and 1,294 adults (aged 18-98 years) living in Hong Kong and Germany, respectively, participated in a web-based study. We fitted our data to a multilevel model in order to take into account the interdependence of domains (i.e., Level 1) within the same individual (i.e., Level 2). RESULTS: The results revealed that reporting higher COVID-19 worries were associated with pandemic-induced aging preparation, and this association was particularly apparent for Germans in comparison to those from Hong Kong. When domains were specified, this cultural difference appeared significantly stronger for the domains of care, connectedness, and end-of-life than finances and housing. DISCUSSION: Findings imply that worrying about the COVID-19 pandemic predicts people to engage in aging preparation particularly in the culture and domains most affected by the pandemic. These results from those worried about the virus may be attributed to the increased self-relevance to the topic and hence motivation.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Coping behavior; End-of-life; Future care needs; Social relations

Daily Experiences of Subjective Age Discordance and Well-Being - Bellingtier, Jennifer A.; Rupprecht, Fiona; Neupert, Shevaun D.; Lang, Frieder (Psychology and Aging, 2021)
Subjective age discordance (SAD) captures the difference between how old one feels and how old one would ideally like to be. We investigated the presence, strength, and fluctuation of this discordance in daily life as well as its relationship to various indicators of physical and psychological well-being with an 8-day diary study. Participants were 116 older and 107 younger adults who completed daily measures of felt age, ideal age, positive and negative affect, physical symptoms, and stressors. We operationalized SAD as felt age minus ideal age divided by chronological age and compared the utility of this discordance to the more established proportional discrepancy of felt age from chronological age. Daily SAD was present in both age groups, such that individuals idealized younger ages than they felt. This discordance was larger in older than younger adults, although younger adults exhibited more daily fluctuations in SAD. Within-person increases in SAD were associated with lower positive affect, whereas larger SAD at the between-person level was associated with more physical symptoms and stressors. These relationships were over and above the associations of felt and chronological age with the outcomes suggesting the utility of daily SAD for understanding daily physical and psychological well-being.
CRIS-Team WoS Importer:2021-09-24

Motivation for Longevity Across the Life Span: An Emerging Issue - Lang, Frieder; Rupprecht, Fiona (Innovation in Aging, 2019)
Over the past decades, increases in life expectancy in most modern societies have raised questions about whether and to what extent individuals value possible extensions of their personal lifetime. In this vein, a new field of research emerged that investigates the determinants, concomitants, and consequences of longevity values and personal preferences for an extended lifetime across adulthood. Based on a review of available theoretical and empirical work, we identified 3 mindsets on the challenges and potentials of human longevity common in research as well as personal views: (a) an essentialist mindset that builds on ideal principles of an infinite life, aimed at conquering or significantly postponing a biologically determined aging process, (b) a medicalist mindset that appraises aging as being primarily based on quality of health, and (c) a stoicist mindset that associates longevity and lifetime extension with the experience of grace and meaning. In this regard, we submit that motivation for longevity and its behavioral consequences differ depending on what mindsets individuals adopt in a given developmental context. We suggest that mindsets of longevity motivation are embedded in personal belief systems (e.g., death acceptance) that may depend on health, and on context influences (e.g., culture). Mindsets of longevity motivation may be related to differences in health behavior and late-life preparation. We illustrate such ideas with an exploratory analysis from a cross-cultural data set. We discuss the possible implications of these mindsets of longevity motivation for the aging sciences, and with regard to individual ways of approaching old age.
CRIS-Team WoS Importer:2019-10-04

Perceived personal deadlines for late-life preparation across adulthood - Lang, Frieder; Rupprecht, Fiona (European Journal of Ageing, 2020)
Throughout adulthood, individuals follow personal timetables of deadlines that shape the course of aging. We examine 6-year-longitudinal data of perceived personal deadlines for starting with late-life preparation across adulthood. Findings are based on a sample of 518 adults between 18 and 88 years of age. Multilevel regression analyses were conducted to explore changes in personal deadlines for preparation in five domains (i.e., finances, end of life, housing, social connectedness, caregiving) in relation to calendar age, self-rated health, subjective position in life, and sociodemographic variables. Findings suggest that personal deadlines for starting preparatory activities differ depending on calendar age and domain of late-life preparation. Older adults as compared to younger adults are likely to report narrower deadlines for beginning with late-life preparation. Perceived deadlines for late-life preparation were furthermore found to be preponed and slightly dilated over time. Findings suggest that depending on age-graded opportunity structures, individuals flexibly adjust their personal deadlines for late-life preparation.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Domain specificity; End of life; Perceived deadlines; Preparation for old age; Subjective position in life

Personal Ideals of Aging and Longevity: The Role of Subjective Discordances - Rupprecht, Fiona; Lang, Frieder (Psychology and Aging, 2020)
Following theoretical models on wishful thinking, we investigated (a) whether personal aging ideals are discordant from self-perceptions of aging, (b) how such aging discordances evolve across adulthood, (c) whether current aging discordances are related to anticipated future aging discordances, and (d) whether aging discordances are related to a lower psychological well-being. We captured subjective age discordance (SAD) as the discrepancy between current perceived age and ideal age, and we captured subjective life-expectancy discordance (SLED) as the discrepancy between perceived life expectancy and ideal life expectancy. For the analyses, we used cross-sectional data from 1,015 individuals (M = 40.0 years, SD = 17.9 years; 52.1% women) and 2-year longitudinal data from 258 individuals (M = 55.3 years, SD = 17.3 years; 70.5% women). Both aging discordances were clearly present across the adult life span; that is, ideal ages were lower than perceived ages, and ideal life expectancies were higher than perceived life expectancies. A stronger SLED was associated with a stronger SAD, both cross-sectionally and longitudinally. Both discordances were also associated with lower psychological well-being in the cross-sectional analyses. Over time, lower life satisfaction predicted increases in SAD, and SLED predicted increases in negative affect. The results indicate that SAD and SLED are both highly prevalent and potentially functional because they seem to be related to psychological well-being. The discussion focuses on SAD and SLED as constructs for future research, their antecedents, and potential consequences.
CRIS-Team WoS Importer:2020-05-02

The Role of Personality in Becoming Aware of Age-Related Changes - Rupprecht, Fiona; Dutt, Anne J.; Wahl, Hans-Werner; Diehl, Manfred K. (GeroPsych, 2019)
Awareness of age-related change (AARC) refers to an individual's conscious knowledge about the gains and losses resulting from growing older. Personality traits reflect dispositional patterns of behavior, perception, and evaluation and should therefore influence the experience of AARC. The 4.5-year longitudinal study examines this association between personality traits and AARC in a sample of 423 individuals aged 40 to 98 years (M = 62.9 years) using latent change analyses. After controlling for sex, health, and education, a different pattern of associations for cross-sectional vs. longitudinal relations. Cross-sectionally, neuroticism was positively related to AARC losses, whereas openness, conscientiousness, and neuroticism were positively related to AARC gains. Longitudinally, the impact of personality traits on change in AARC was rather limited with only higher conscientiousness acting as a predictor of decreases in AARC losses over time. Overall, the findings add to the existing literature on associations between personality traits and subjective aging. Specifically, the results indicate that personality traits are differentially related to awareness of age-related gains in comparison to awareness of age-related losses.
CRIS-Team WoS Importer:2019-06-18